Pola Pengembangan English Dictionary for Early Childhood Education - Amalia, Taranindya Zulhi (Association of Indonesian Islamic Kindergarten Teachers Education Study Program, 2018)
basic English skills, 2) analyze the development pattern of the English Dictionary for Early Childhood Education, and 3) classify the constraints and its solutions. The primary data sources of this field research that uses qualitative descriptive approach is the head of TKIT, curriculum section, and ustadzah. While secondary data is the TKIT language dictionary, pictorial dictionary, institutional documentation and references related to the dictionary development. The data collection techniques are moderate participatory observation, semi-structured interviews, and documentation. The results show that: 1) The development pattern of basic English skills are introduction of English vocabularies in local content refers to themes and sub-themes that contain local wisdom values in 2013 PAUD curriculum and their repetitions in circle center time, theme tops and end of the month as well as morning review, and in the afternoon before go home also the Three Languages Dictionary, 2) The development patterns are: proposing vocabulary by a dictionary compilation team, collection of proposed vocabulary translated into English and Arabic, pronunciation of vocabulary, assistance with difficult vocabulary translations by English experts, and dictionary writing, while 3) the constraints are: in terms of time; there is no solution but the dictionary evaluation agenda based on changes in themes and sub themes; in terms of changes in curriculum themes, the solution is to choose general themes, in the term of no budgetary aspect for dictionary evaluation of dictionaries, the solution is to do the allocatio;, in terms of human resources that do not have any language background, the solution is sharing experiences with other stakeholders, especially those who specifically have  vision and mission/predominance on language.